2010
DOI: 10.1111/j.1365-2982.2010.01553.x
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of ghrelin and des-acyl ghrelin on the lumbo-sacral defecation center and regulation of colorectal motility in rats

Abstract: It is concluded that acylation of the ghrelin peptide is essential to promote propulsive contractions of the colorectum and that des-acyl ghrelin opposes this effect. At most other sites of ghrelin action, des-acyl ghrelin either has no effect or it mimics ghrelin. This is the first evidence that non-acylated ghrelin opposes the action of the acylated peptide in the spinal cord.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 43 publications
2
52
0
1
Order By: Relevance
“…Unlike the dysreflexic blood pressure increases that occur when the colon is distended in spinal cord-injured rats, 17 the events in the colon and the blood pressure changes that are observed in response to ghrelin agonists in rats without SCI are independent. 5,9 When they are applied at sites rostral to the defecation centers in normal animals (and rostral to the site of SCI used in the current experiments), ghrelin receptor agonists only elicit blood pressure responses (maximal blood pressure effects are from T9 to T12) and only small blood pressure increases are elicited from the levels of the defecation centers at L1 to L3. 9 Moreover, the effects on the colon can be blocked pharmacologically without affecting the blood pressure increases that occur when ghrelin receptors are activated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Unlike the dysreflexic blood pressure increases that occur when the colon is distended in spinal cord-injured rats, 17 the events in the colon and the blood pressure changes that are observed in response to ghrelin agonists in rats without SCI are independent. 5,9 When they are applied at sites rostral to the defecation centers in normal animals (and rostral to the site of SCI used in the current experiments), ghrelin receptor agonists only elicit blood pressure responses (maximal blood pressure effects are from T9 to T12) and only small blood pressure increases are elicited from the levels of the defecation centers at L1 to L3. 9 Moreover, the effects on the colon can be blocked pharmacologically without affecting the blood pressure increases that occur when ghrelin receptors are activated.…”
Section: Discussionmentioning
confidence: 99%
“…9 Moreover, the effects on the colon can be blocked pharmacologically without affecting the blood pressure increases that occur when ghrelin receptors are activated. 5 It remains possible that if the SCI had been above T5, a level that in rats severs the bulbospinal pathways controlling the splanchnic circulation, hyper-reflexic blood pressure responses would have been elicited. We have been unable to locate any published data that indicate that centrally penetrant ghrelin receptor agonists increase blood pressure in human.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, consistent reports of effects of ghrelin on colonic contractility have been lacking despite tissue expression of GRLN-R [58][59][60][61][62]. Animal studies in dogs and rodents have shown no effect on colonic motility with intravenous administration of ghrelin, while central or intraperitoneal administration has demonstrated stimulation of colonic motility reflected by decreased colonic transit time and increased intracolorectal pressures and fluid output [63][64][65][66][67], suggesting that effects of ghrelin or ghrelin agonists on colonic motility are centrally mediated, requiring crossing of the blood brain barrier.…”
Section: Effects Of Ghrelin On Gastrointestinal Motilitymentioning
confidence: 99%